Multimodel LQ controller design for variable-speed and variable pitch wind turbines at high wind speeds. (1st January 2012) - Khezami, Nadhira; Guillaud, Xavier; Braiek, Naceur Benhadj
This paper focuses on designing a multimodel linear quadratic (LQ) controller for variable-speed horizontal axis wind turbines. Those turbines use blade-pitch and electromagnetic torque control to meet specified objectives for three regions of operation. We aim in this paper to use the blade-pitch control in the high wind speed operating zone. The controller is then designed in order to optimise a trade-off between two main control objectives which are alleviation of drive train dynamic loads and maximisation of energy efficiency. It is thereafter implemented for a deloaded operation to provide an additional operating reserve necessary to increase the effective participation of the wind turbines in the system frequency regulation. A 2MW wind turbine is considered to illustrate the good performances brought by the proposed approach by presenting and discussing the simulation results.